Group participation and the risk of functional decline in later life: A Prospective Cohort Study - Makoto Kaneko PhD; Fumihiro Saitoh PhD; Hotaka Hara MD; Takako Motomura; Kumiko Maruyama; Yumiko Okamoto BA; Hisako Kuribayashi; Kouichi Imai LLB; Katsunori Kondo PhD (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
Although group participation benefits older adults’ health, its effects may vary by group type. The Japanese Health and Welfare Co-operative (Hew Co-op) organises peer-led group participation called ‘Han Kai’ meetings to promote health literacy, but the impact of Han Kai participation on health indicators remains unexplored. This study aimed to examine whether the frequency and duration of Han Kai participation were associated with risk of functional disability. This was a prospective cohort study conducted in Japan between 2018 and 2022. The participants were Han Kai members aged ≥ 65 years who did not receive a Long-Term Care certification. The exposure variables were the frequency of participation in Han Kai per year and the years of participation in 2018. The main outcome was a risk assessment scale score for predicting incident functional disabilities in 2022. Multivariate linear regression was conducted to adjust for covariates. In the study, 2359 older adults participated. Overall, the frequency of Han Kai participation was not significantly associated with disability risk scores. However, participants with ≥10 years of involvement had significantly lower scores (β = –1.95, 95% CI: –3.64 to –0.26, P  = .024). Among those aged ≥ 75 years, both frequency and duration showed a significant inverse association with risk scores, with a dose–response relationship. Sustained participation in peer-led group meetings such as Han Kai may help mitigate functional decline, particularly among the oldest age groups. These findings support policies that promote long-term community engagement as part of healthy ageing strategies.